(untitled) (Al-Mansour Journal, 2022)
Alexander Murray Palmer Haley (1921-1992) was born in Ithaca, New York. In his ancestral village of Juffure, Haley listened to a tribal historian recount how Kunta Kinte, Haley’s ancestor and the protagonist of his book, was captured and sold into slavery. When Haley finally published Roots in 1976, it caused a national sensation. Haley always maintained that the goal of his writing, and that of his life was simply to advance the oppressed cause of African people. The Paper aim at discussing the ideological and cultural perspectives of trafficking African people. It attempts to expose the actual situation of slaved people ,and their struggle to survive. The Paper is divided into two sections and a conclusion. The first section focuses on the definition of human trafficking. It is concerned with the emergence of African- American literature. Section two concerns itself with the life and works of Alex Haley. It focuses on the issue of slavery or trafficking African people presented by Kunta and his predecessors in Roots. The conclusion sums up the findings of the Paper.